Thriving, Persisting, or Agonizing: Integrated Math Anxiety Experiences of University Students in Introductory Geoscience Classes - Julie Sexton; Dina London; Molly M. Jameson; Jennifer M. Wenner (Education Sciences, 2022)
Many factors may contribute to women being underrepresented and marginalized in college-level geoscience majors. Limited research has examined students’ math anxiety as a possible factor. To address the dearth of research, we conducted a qualitative study to explore the math anxiety experiences held by students in college-level geoscience classes. Through analysis of students’ written math narratives, we identified three themes capturing students’ integrated math anxiety experiences (IMAEs), which integrated students’ feelings, physiological reactions, and thoughts. Students with Thriving IMAEs liked math and had positive assessments of themselves in math. Students with Agonizing IMAEs had negative feelings and thoughts about math and experienced negative physiological reactions. Students with Persisting IMAEs had positive and negative feelings and thoughts, but thought that, ultimately, they could persist in math. A higher percentage of women than men held Agonizing IMAEs, and a lower percentage of women than men held Thriving IMAEs. Students in introductory geoscience classes had a range of IMAEs, which may have an important role in their success in class and in their decisions to take additional geoscience classes.